Pengembangan Bakat dan Minat Peserta Didik Di Madrasah Ibtidaiyah Miftahul Muna Kesilir Banyuwangi - Zainal Abidin; Nasirudin Nasirudin (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Jember, 2021)
Each student has different potentials from one another, because each person is indeed born with a variety of different talents and has brought out his or her own nature, namely good nature that encourages tawhid and other natural qualities in the form of various innate potentials such as talents, intellectual abilities and others. The research approach used is a descriptive qualitative approach with the type of case study. The techniques used are interviews, observation, and documentation. While the validity of the data used triangulation of techniques and sources. The results of this study indicate: (1) Mina talents at MI Miftahul Muna through recruitment where students choose and register themselves to take part in the extracurricular program. Such as: drumband, dance, qiroat, scout, Pencak Silat, Chess, Volleyball, football, hadrah, singing, fashion, culinary, and calligraphy. (2) Interest talent planning, namely: Learning Implementation Plan, preparing experts who are competent in their fields as well as students recruited through extracurricular registration. Except for the drum band in this case bringing in experts from outside. (3) Implementation of talent and interest development at Madrasah Ibtidaiyah Miftahul Muna Kesilir, which is carried out once a week every Friday unless the drumband is held on Fridays and Sundays and if you want to appear at certain events, you can adjust the trainer's schedule or not. (4) Supervision is carried out directly at the time of the activity and some is carried out in an indirect way such as in this drumband activity because it brings in a trainer and is reported to the Madrasah Head. Keywords: Development; Talents and Interests; Students Setiap peserta didik memiliki potensi yang berbeda-beda antara satu dengan yang lain, karena setiap orang memang dilahirkan dengan berbagai bakat yang berbeda-beda dan telah membawa fitrahnya masing-masing, yaitu fitrah baik yang mendorong bertauhid maupun fitrah lainnya dalam bentuk berbagai potensi bawaan seperti bakat, kemampuan intelektual dan lain-lain. Pendekatan penelitian yang digunakan adalah pendekatan kualitatif deskriptif dengan jenis studi kasus, Adapun tehnik yang digunakan adalah wawancara, observasi, dan dokumentasi. Sedangkan keabsahan data menggunakan triangulasi tehnik dan sumber. Hasil penelitian ini menunjukkan: (1) Pemetaan bakat mina di MI Miftahul Muna melalui perekrutan dengan peserta didik memilih dan mendaftarkan diri mengikuti program ekstrakurikuler. Seperti: drumband, tari, qiroat, pramuka, Pencak Silat, Catur, Bola Volly, Sepak Bola, hadrah, menyanyi, tata busana, tata boga, dan kaligrafi. (2) Perencanaan bakat minat, yaitu: Rencana Pelaksanaan Pembelajaran, menyiapkan tenaga ahlinya yang berkompeten dibidangnya serta peserta didik yang direkrut melalui pendaftaran ekstrakurikuler. Kecuali drum band dalam hal ini mendatangkan tenaga ahli dari luar. (3) Pelaksanaan pengembangan bakat dan minat di Madrasah Ibtidaiyah Miftahul Muna Kesilir yaitu dilaksanakan seminggu sekali setiap hari jum’at kecuali drumband dilaknakan hari Jum’at dan Minggu serta kondisional jika mau tampil pada event-event tertentu menyesuaikan jadwal pelatih bisa atau tidak. (4) Pengawasan dilakukan secara langsung pada saat kegiatan dan ada pula yang dilakukan dengan cara tidak langsung seperti yang dilakukan di kegiatan drumband ini karena mendatangkan pelatih dan dilaporkan ke Kepala Madrasah. Kata Kunci: Pengembangan; Bakat dan Minat; Peserta didik